A manganese(i)tricarbonyl-catalyst for near room temperature alkene and alkyne hydroarylation. Issue 44 (3rd November 2022) - Choudhary, Shweta; Cannas, Diego M.; Wheatley, Matthew; Larrosa, Igor
Abstract : A Mn(i )-catalyst for hydroarylation reactions, MnBr(CO)3 (MeCN)2, avoids the formation of the off-cycle manganacycle-(CO)4 species responsible for low catalyst activity typical of MnBr(CO)5, leading to mild and broad scope hydroarylation. Abstract : Developing more efficient catalytic processes using abundant and low toxicity transition metals is key to enable their mainstream use in synthetic chemistry. We have rationally designed a new Mn(i )-catalyst for hydroarylation reactions that displays much improved catalytic activity over the commonly used MnBr(CO)5 . Our catalyst, MnBr(CO)3 (MeCN)2, avoids the formation of the off-cycle manganacycle-(CO)4 species responsible for low catalyst activity, allowing near room temperature hydroarylation of alkenes and alkynes with broad functional group tolerance including late stage functionalisation and diversification of bioactive molecules.